LINC01089 Inhibits Tumorigenesis and Epithelial–Mesenchymal Transition of Non-small Cell Lung Cancer via the miR-27a/SFRP1/Wnt/β-catenin Axis - Li, Xingkai; Lv, Fang; Li, Fang; Du, Minjun; Liang, Yicheng; Ju, Shaolong; Liu, Zixu; Zhou, Boxuan; Wang, Bing; Gao, Yushun (Frontiers in Oncology, 2020)
Long noncoding RNAs (lncRNAs) have emerged as regulators of gene expression, and play critical regulatory roles in diverse biological functions and diseases, including cancer. In this study, we report downregulation of LINC01089 in non-small cell lung cancer (NSCLC) samples, relative to adjacent non-tumor tissues, and demonstrate its role in inhibition of proliferation, migration, and epithelial-mesenchymal transition (EMT) of NSCLC cells. Mechanistic analysis indicate that LINC01089 acts as a sponge for miR-27a, regulating its expression in NSCLC. Interestingly, LINC01089 mediated upregulation of SFRP1 expression by inhibiting the Wnt/β-catenin-EMT pathway, and inhibiting the epithelial-mesenchymal transition of NSCLC via sponging miR-27a. Overall, our findings highlight LINC01089’s tumorigenic role and regulatory mechanism in NSCLC thereby suggesting its potential as a therapeutic target for managing NSCLC